Low-temperature sintering of a porous SiC ceramic filter using water glass and zirconia as sintering aids. Issue 18 (15th September 2021) - Jiang, Qian; Xie, Yuling; Ji, Lingqian; Zhong, Zhaoxiang; Xing, Weihong
Abstract: The fabrication of porous silicon carbide (SiC) ceramics prepared by existing reaction bonding technology requires high-temperature sintering beyond 1400 °C. We used low-cost industrial grade water glass and zirconia as sintering aids to prepare porous SiC ceramic filters to reduce the sintering temperature while improving the commerciality. Additionally, we investigated the effects of different sintering temperatures and the addition of water glass on the samples. Loading water glass and zirconia reduced the sintering temperature to 600 °C. The additive-loaded ceramic filter sintered at 600 °C exhibited an average pore size of 0.58 μm, a porosity of 47.4%, a bending strength reaching 56 MPa, a pure water permeance exceeding 4800 L m −2 h −1 bar −1, and good acid corrosion resistance. In addition, the SiC filter prepared at 1000 °C showed good chemical resistance and an average pore size of 0.75 μm as well as mechanical strength and pure water permeance of over 80 MPa and 6294 L m −2 h −1 bar −1, respectively. The low-cost, high-performance porous SiC ceramic filter exhibits broad commercial application prospects in water treatment. Highlights: A liquid sintering aid was used to promote reaction sintering of the SiC filter. With water glass, the sintering temperature of SiC filter was reduced to 600 °C. High performance porous SiC ceramic filter was prepared in a low-cost way. SiC ceramic filter sintered at 1000 °C exhibited good chemical resistance.